International development law rule of law, human rights, and global finance - Sarkar, Rumu. (New York ; Oxford : Oxford University Press, 2009)
This theoretical and practical overview of the international legal architecture between developing countries and advanced nations is divided into two parts, the first providing a theoretical overview of the philosophical implications of international development law principles; the second deals with international financial architecture.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Economic development projects -- Law and legislation; Law and economic development; Loans, Foreign -- Law and legislation